2009
DOI: 10.1016/j.biopsych.2009.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Sexual Abuse Is Associated with Reduced Gray Matter Volume in Visual Cortex of Young Women

Abstract: Objective Childhood sexual abuse (CSA) has been associated with alterations in brain morphology using region of interest analyses that have focused on stress sensitive target regions. This study was designed to ascertain the effects on gray matter volume (GMV) of exposure to CSA in a healthy population of young adult college students selected based on the history of exposure regardless of psychiatric outcome. Voxel-based morphometry (VBM) provided unbiased delineation of most significantly affected brain regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
140
4
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(160 citation statements)
references
References 66 publications
(73 reference statements)
8
140
4
3
Order By: Relevance
“…Hence, our findings are more applicable to the remaining 43%, who experience WDV as their sole form of maltreatment. Studies of individuals exposed to single types of maltreatment have primarily identified differences in sensory regions or pathways [8,11,48,51]. This observation stands in contrast to findings from other studies, including our own, that combine subjects exposed to one or more types of abuse into a single group.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…Hence, our findings are more applicable to the remaining 43%, who experience WDV as their sole form of maltreatment. Studies of individuals exposed to single types of maltreatment have primarily identified differences in sensory regions or pathways [8,11,48,51]. This observation stands in contrast to findings from other studies, including our own, that combine subjects exposed to one or more types of abuse into a single group.…”
Section: Discussioncontrasting
confidence: 63%
“…This approach has been useful in revealing similarities and differences between the neurobiological correlates of exposure to childhood sexual abuse [48,57], parental verbal abuse [11,51], WDV [8] and harsh corporal punishment [12,58]. This strength is also a limitation as many abused individuals, particularly those involved in the mental health system, experienced multiple forms of maltreatment.…”
Section: Discussionmentioning
confidence: 99%
“…These authors implemented the cortical parcellation method to validate their whole-brain VBM analysis. 51 However, we chose to apply the methods in an opposing order. Apart from its popularity in clinical research, there has been emerging concern about some limitations of VBM.…”
Section: Discussionmentioning
confidence: 99%
“…adulthood and intensity as well as timing of stress may modulate cortical affective processing in different ways (Lupien et al, 2009). It seems also possible that dampened cortical activation reflects stressrelated functional brain changes, as Tomoda et al (2009) found reduced grey matter volume in primary and secondary visual cortices in subjects with a history of childhood sexual abuse. Moreover, white matter tract abnormalities indicating alterations in neural pathways have been associated with parental verbal abuse (Choi et al, 2009).…”
Section: Discussionmentioning
confidence: 96%